Determination of a pH threshold for dark cutting beef based on visual evaluation by Asian consumers. (February 2021) - Zhang, Yining; Holman, Benjamin W.B.; Mao, Yanwei; Chen, Xue; Luo, Xin; Hopkins, David L.; Zhang, Yimin
Abstract: This study defined the pH threshold for dark cutting beef of Asian consumers using a web-based survey and examined their preferences for beef appearance. Ninety individual images of beef steaks with different pH values were randomly selected to be scored by 4322 respondents. Gender, age and beef eating habits of respondents were found to impact on color preferences. With respondent's visual score of 4 set as the acceptance threshold, linear regression analysis between visual scores and beef instrumental colorimetrics, showed that the acceptance thresholds of instrumental color values were L*  ≥ 31.4, a*  ≥ 16.4, b*  ≥ 6.5, chroma ≥17.4 and hue ≥22.5. These corresponded to pH threshold values of 6.11, 6.20, 6.28, 6.25 and 6.29, respectively. This pH benchmark (6.11 to 6.29) for dark cutters is higher than pH thresholds applied in most countries, indicating that Asian consumers prefer darker meat than expected, however, the likely tenderness of beef with pH's at this level merits consideration.